Forensic parameter and parental lineage investigation of TPA-25 element in Kelantan-Malay and Jawa-Malay sub-ethnic groups in peninsular Malaysia / Nurul Syafika Muslimin - Muslimin, Nurul Syafika (2017)
A Malay is defined as someone who speaks the Malays Language, follows Malays culture, or one of the parents was born in Malaysia before independence 1957. In Peninsular Malaysia, the Malays consist of multi sub-ethnic group believed to have different ancestral origins based on their migrations centuries ago. The estimation of Malaysian population is approximately 32 million individuals with different sub-ethnic groups. The DNA profiling for each individual in Malaysia is not recorded, making Malaysia lacking in genetic data of its own citizens.